The Riverbanks in the Center - Cirillo, José (Farol, 2025)
This thematic dossier is linked to the academic debates of the 1st Symposium on Riverside Landscapes, which arose from the need to understand the aesthetic and urban relationships surrounding the development of art and the city in the context of the main cities bordering the rivers, as presented by the main cities of Espírito Santo and our Brazilian, Portuguese, and Spanish partners.